Short story theories : a twenty-first-century perspective - Pâtea, Viorica (Rodopi, 2012)
"Short Story Theories: A Twenty-First-Century Perspective problematizes different aspects of the renewal and development of the short story. The aim of this collection is to explore the most recent theoretical issues raised by the short story as a genre and to offer theoretical and practical perspectives on the form. Centering as it does on specific authors and on the wider implications of short story poetics, this collection presents a new series of essays that both reinterpret canonical writers of the genre and advance new critical insights on the most recent trends and contemporary authors. Theorizations about genre reflect on different aspects of the short story from a multiplicity of perspectives and take the form of historical and aesthetic considerations, gender-centered accounts, and examinations that attend to reader-response theory, cognitive patterns, sociolinguistics, discourse analysis, postcolonial studies, postmodern techniques, and contemporary uses of minimalist forms. Looking ahead, this collection traces the evolution of the short story from Chaucer through the Romantic writings of Poe to the postmodern developments and into the twenty-first century. This volume will prove of interest to scholars and graduate students working in the fields of the short story and of literature in general. In addition, the readability and analytical transparence of these essays make them accessible to a more general readership interested in fiction."--Resumé vydavatele
Keywords: povídka; literárněvědné rozbory; short stories; literary criticism and history; eseje; essays